2002
DOI: 10.1038/sj.bmt.1703607
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-transplant positron emission tomography (PET) using fluorine-18-fluoro-deoxyglucose (FDG) predicts outcome in patients treated with high-dose chemotherapy and autologous stem cell transplantation for non-Hodgkin's lymphoma

Abstract: Summary:We investigated the predictive value of sequential FDG PET before and after high-dose chemotherapy (HDT) and autologous stem cell transplantation (ASCT) in 24 patients suffering from non-Hodgkin's lymphoma (NHL). FDG PET was performed at baseline, after three cycles of induction therapy, before and after HDT with ASCT. Response assessment from sequential PET scans using standardized uptake values (SUV) was available in 22 patients at the time of transplantation. Partial metabolic response (PMR) was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 18 publications
1
55
0
2
Order By: Relevance
“…More recently, some studies indicated that 18 FDG-FDG-PET also provides useful information about disease status before ASCT and even allogeneic stem cell transplantation in relapsed or refractory HL and non-Hodgkin's lymphoma, with a significant correlation between pretransplant PET status and prognosis [20][21][22][23][24][25][26]. CT scan is the most used in restaging lymphoma; however, some authors reported that history and physical examination could be the standard approach to follow-up because in most cases early recurrence is first suspected by the patient himself or by the physician, even with routine screening including CT scans [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some studies indicated that 18 FDG-FDG-PET also provides useful information about disease status before ASCT and even allogeneic stem cell transplantation in relapsed or refractory HL and non-Hodgkin's lymphoma, with a significant correlation between pretransplant PET status and prognosis [20][21][22][23][24][25][26]. CT scan is the most used in restaging lymphoma; however, some authors reported that history and physical examination could be the standard approach to follow-up because in most cases early recurrence is first suspected by the patient himself or by the physician, even with routine screening including CT scans [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In another study, investigators suggested that FI can identify patients with high-risk lymphoma who might benefit from HDCT/ASCT as front-line therapy, considering that sustained biologic response is an important feature before transplantation. 23 Other studies assessed the value of FI before ASCT; however, many studies PFS indicates progression-free survival; OS, overall survival; 95% CI, 95% confidence interval; M, male; F, female; LD, lymphocyte depleted; LP, lymphocyte predominant; MC, mixed cellularity; NS, nodular sclerosis; CRD1, first complete response duration; END, extranodal disease; ESHAP, etoposide, methylprednisolone, cytarabine, and cisplatin; ASHAP, doxorubicin, methylprednisolone, cytarabine, and cisplatin; CR, complete response; CRu, unconfirmed CR; ASCT, autologous stem cell transplantation; PET, positron emission tomography; Ga, gallium; PR, partial response; FI, functional imaging; pos, positive; neg, negative.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis by Cremerius et al, 9 16 of 23 patients achieved a CMR, 7 patients did not. Median PFS was 38 versus 14 months, respectively (not statistically significant).…”
Section: Post Transplant Fdg Pet Scanning In Non-hodgkin's Lymphomamentioning
confidence: 99%
“…The first published prospective analysis of patients undergoing FDG PET scans pre-SCT was reported by Cremerius et al 9 In total, 23 of the 24 patients had newly diagnosed lymphoma and were scheduled to receive up front chemotherapy followed by ASCT. In this study, patients underwent FDG PET scanning at baseline, after three cycles of induction therapy, before and after ASCT.…”
Section: Utilization Of Fdg Pet Pretransplant In Nhlmentioning
confidence: 99%